THE EFFECT OF TRUST, BRAND AWARENESS, AND SOCIAL PIETY IN DONATION DECISIONS THROUGH DIGITAL PLATFORMS - Dahlia Bonang; Muhammad Baihaqi (ULUL ALBAB Jurnal Studi Islam, 2022)
This article identifies the effect of trust, brand awareness, and social piety before doing donation using the Fintech platform. Therefore, this explanatory research examined the influence of four variables. The data were collected through a purposive sampling technique involving 250 societies across Lombok Island as respondents, as well as applying a case study approach. The data analysis technique is implemented through SEM (Structural Equation Modelling). The article shows a positive and significant impact among trust, brand awareness, and social piety in donation decisions through the fintech platform. However, brand awareness and trust do not affect social piety. Hence, this article recommends the fundraising institutions that actively collect funds through fintech platforms to always prioritize the openness principle in managing public funds. A transparent attitude can increase public trust to utilize the platform whenever they want to channel funds spontaneously.